Response of Genotypes and Transplanting Schedule in Relation to Seed Quality in Tomato - MOHINDER KAUR; J.S. KANWAR (Seed Research, 2026)
Studies were conducted to investigate the response of six tomato genotypes (VFN 8, ACC 8, W 321, Punjab Chhuhara, ACC 2 and 1-181) under four planting dates (November 20, December 5, December 20 and January 5) on seed quality in tomato at Punjab Agricultural University, Ludhiana during 2002-2003. Highest fruit yield (879.82 q/ha), 1000-seed weight (2.81 g) and seed vigour index (1399.22) were recorded in November 20 planted crop, whereas fruit weight (85.04 g) and number of seeds per fruit (98.97) were highest in December 5 transplanted crop. Germination percentage of 79.62% in November 20 planted crop was at par with December 5 planted crop (78.78%). Among genotypes, maximum mean fruit yield (747.73 q/ha) and seeds number/fruit (132.98) were obtained in ACC-8, whereas W-321 had the highest 1000-seed weight. The genotype I-181 had maximum seed vigour index (1420.12). The seed germination percentage of genotypes differed non-significantly. The interaction between planting dates and genotypes was non-significant for 1000-seed weight, germination percentage and seed vigour index.